2016
DOI: 10.1515/jppr-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Changes of antioxidant enzymes of mung bean [Vigna radiata (L.) R. Wilczek] in response to host and non-host bacterial pathogens

Abstract: Abstract:The natural resistance against the majority of potential pathogens that exist in most plant species is known as non-host resistance. Several reports suggest the role of antioxidant enzymes in non-host resistance. We assayed the expression or activity of four scavenging enzymes during non-host pathogen-plant interaction (Xanthomonas hortorum pv. pelargonii/mung bean) and host pathogen-plant interaction (Xanthomonas axonopodis pv. phaseoli/mung bean). The expression of superoxide dismutase (SOD) and asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…; Chen et al. ; Farahani and Taghavi ). Similarly, GPX has also been observed to increase in plants that are infected such as sunflowers infected by downy mildew (Herbette et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chen et al. ; Farahani and Taghavi ). Similarly, GPX has also been observed to increase in plants that are infected such as sunflowers infected by downy mildew (Herbette et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we directly attribute the higher ROSscavenging enzyme activity in infected samples to the higher ROS radical activities in infected samples. Ascorbate peroxidase activity has been shown to increase in plants infected by pathogens such as apricot, wheat and mung bean (Hern andez et al 2001;Chen et al 2015;Farahani and Taghavi 2016a). Similarly, GPX has also been observed to increase in plants that are infected such as sunflowers infected by downy mildew (Herbette et al 2003).…”
Section: Ros-scavenging Assaysmentioning
confidence: 99%
“…Higher levels of PO and PPO activity was observed in M. phaseolina infection treated with the bioformulation combination of plant growth promoting bacteria (P. fluorescens) and biocontrol agents (Trichoderma or Bacillus) than the plants treated with single biocontrol agent (Thilagavathi et al, 2007). Mechanism of SAR were studied for bacterial (Dutta et al, 2005;Farahani and Taghavi, 2016) and viral diseases (Rashid et al, 2004) of mungbean, but study regarding fungal diseases are still meager. Thus, more investigations are required to understand the SAR and ISR mechanisms in the interactions between mungbean and fungal diseases.…”
Section: Botanical Fungicides and Bio-stimulantsmentioning
confidence: 99%
“…POD activity is stimulated by both bacterial plant pathogens (Farahani and Taghavi 2016;Jang et al 2004) and beneficial rhizobacteria (Lavania et al 2006), but less is known about how LPS from these bacteria affect POD activity. Here we compared the effect of LPS on POD activity and found that while both types of LPS increased POD activity, LPS from the pathogenic bacteria were associated with larger increases in POD activity, suggesting that plants may be able to distinguish between LPS from PGPR and bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%